The impact of surgical assistants on postoperative complications in robot-assisted Ivor-Lewis esophagectomy for esophageal carcinoma - Wang, Xipeng; Lu, Tong; Guo, Wei; Cao, Yuqin; Li, Chengqiang; Li, Hecheng (Frontiers in Surgery, 2024)
AimThis study examines the impact of different surgical assistants on robot-assisted Ivor Lewis esophagectomy. It aims to establish a foundation for refining surgical practices and improving patient outcomes.MethodsThe study included patients aged 18–75 with resectable esophageal squamous cell carcinoma, treated at Ruijin Hospital's Department of Thoracic Surgery (May 2015–November 2023). The robot-assisted Ivor Lewis esophagectomy (RAILE) was executed on a cohort of 97 patients, led by a highly experienced thoracic surgeon and assisted by three additional thoracic surgeons. Postoperative complications, including anastomotic leakage, pulmonary and cardiac events, as well as hemorrhages, were assessed using the Clavien–Dindo classification. The da Vinci Surgical System was used, and statistical analysis was performed using SPSS 20.0, with P = 0.05 as the significance threshold.ResultsOf the 97 patients, 50 were in Group A, 23 in Group B, and 24 in Group C. No major differences were found in anastomotic leakage, pneumonia, pneumothorax, severe cardiac complications, chylothorax, and vocal cord paralysis. Assistant C recorded a higher frequency of pleural effusion (45.8%) vs. Assistants A (16.0%) and B (21.7%). The duration of hospital stay was similar across groups, with median durations of 10 days for A, 8 days for B, and 10 days for C.ConclusionThe study found no significant overall impact of different surgical assistants on postoperative complications in robot-assisted Ivor Lewis esophagectomy. However, pleural effusion rates varied, possibly due to surgical procedure and patient's condition and may be relevant to the assistant's procedure. Future research should involve larger, more varied samples to further validate and refine these findings.